2015
DOI: 10.3889/oamjms.2015.052
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Patients with Systemic Lupus Erythematosus in Serbia: Correlation with Disease Activity and Clinical Manifestations

Abstract: BACKGROUND:Numerous studies indicate potential role of vitamin D as an important factor in the development of many autoimmune diseases including systemic lupus erythematosus (SLE). Patients with SLE are especially prone to the development of vitamin D deficiency due to the nature of their illness.AIM:The aims of our study were to determine the prevalence of vitamin D insufficiency and deficiency in patients with SLE in Serbia, to identify clinical variables associated with vitamin D status and to examine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
6
13
1
Order By: Relevance
“…In contrast, many other studies did not find this association [2,7,29]. The discrepancy between the findings of these studies and the present study can be attributed to the characteristics of the enrolled population since patients with VD supplements were not excluded from these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, many other studies did not find this association [2,7,29]. The discrepancy between the findings of these studies and the present study can be attributed to the characteristics of the enrolled population since patients with VD supplements were not excluded from these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in agreement with our findings, previous studies observed that the average serum VD in SLE patients was significantly lower than in the healthy matched controls [2,28]. One study reported that 75% of SLE patients had VD deficiency and 15.2% VD insufficiency [29].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…3 Vitamin D deficiency is more prevalent among South Asian, Middle Eastern and African healthy women exactly as in patients with SLE in these regions. [4][5][6][7] Inadequate VD status can compound the problem of low BMD or osteoporosis, commonly seen in patients with SLE induced by corticosteroids. 8 A longitudinal study in 2012 highlighted the importance of prevention and treatment of VD deficiency and osteoporosis in SLE patients, especially those using glucocorticoids or anti-malarial drugs.…”
Section: Introductionmentioning
confidence: 99%